Transportation of high-current charged-particle beam in coaxial undulator with partially shielded cathode in guide homogeneous magnetic field - Tishchenko, A.S.; Yatsenko, T.; Ilyenko, K. (Вопросы атомной науки и техники, 2015)
We derive the system of transcendental equations, which gives the equilibrium radii of charged-particle beam and the equilibrium value of square azimuthal momentum of beam boundary in a coaxial magnetic undulator with partially shielded cathode in guide homogeneous magnetic field. We formulate the dynamics equations, which describe the transportation of charged-particle beam. We receive an analytical estimate of the azimuthal and longitudinal momentum of beam boundary. We study the equilibrium and differential equation numerically, compare results received for a coaxial magnetic undulator with shielded and non-shielded cathode and different induction of guide magnetic field. Получена система трансцендентных уравнений, решениями которой являются равновесные радиусы и равновесные значения квадратов азимутальных импульсов границ пучка заряженных частиц в коаксиальном магнитном ондуляторе с частично экранированным катодом в ведущем однородном магнитном поле. Сформулированы динамические уравнения, которые описывают транспортировку пучка заряженных частиц в камере дрейфа. Получены аналитические оценки азимутального и продольного импульсов границ пучка. Численно исследованы уравнения равновесия и динамические уравнения, проведены сравнения результатов в случае экранированного и неэкранированного катодов, а также зависимость от напряженности ведущего магнитного поля. Отримана система трансцендентних рівнянь, рішеннями якої є рівноважні радіуси та рівноважні значення квадратів азимутальних імпульсів меж пучка заряджених частинок у коаксіальному магнітному ондуляторі с частково екранованим катодом у ведучому однорідному магнітному полі. Сформульовані динамічні рівняння, які описують транспортування пучка заряджених частинок у камері дрейфу. Отримані аналітичні оцінки азимутального і повздовжнього імпульсів меж пучка. Чисельно вивчені рівняння рівноваги та динамічні рівняння, проведено порівняння результатів у випадку екранованого та неекранованого катодів, а також залежність від напруги ведучого магнітного поля.